Iron product and surface treatment method thereof

By forming a chemical conversion film containing ferrous oxalate crystals on the surface of the iron product, and forming a composite crystal film layer through secondary conversion and surface finishing, the problems of powdering and environmental pollution in the surface treatment of iron product are solved, the corrosion resistance and adhesion of the product are improved, the process flow is simplified and the generation of wastewater and solid waste is reduced.

CN119913496APending Publication Date: 2025-05-02SHANDONG HAISI SURFACE TREATMENT TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510093297.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

During the surface treatment process of iron products, iron ions are very likely to return and oxidize, resulting in powdering on the membrane surface, which affects the performance of use. The existing process is complex, resulting in a large amount of wastewater and solid waste, resulting in environmental pollution.

Method used

A one-step chemical conversion method of oil removal and rust removal is used to form a chemical conversion film containing ferrous oxalate crystals on the surface of the iron product, and a composite crystal film layer is formed through secondary conversion and surface adjustment to increase the adhesion and corrosion resistance of the resin paint film layer.

Benefits of technology

It effectively solves the problem of insufficient bonding between the surface film layer of the iron product and the resin paint film layer, improves the corrosion resistance and adhesion of the product, simplifies the process flow, significantly reduces the amount of wastewater and solid waste, and reduces the consumption of chemical raw materials and water.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119913496A_ABST
    Figure CN119913496A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of iron product surface pretreatment, and particularly discloses an iron product and a surface treatment method thereof. A layer of chemical conversion film is formed on the surface of the iron product, and the chemical conversion film mainly contains ferrous oxalate crystals. The chemical conversion film is covered with a conversion protection film, and the chemical conversion film and the conversion protection film are compounded to form a crystalline film layer. According to the method, an oil removal and rust removal chemical conversion one-step method is firstly adopted, oil stains and rust on the surface of the ironwork can be removed, a layer of ferrous oxalate crystal chemical conversion film is formed on the surface of the ironwork, then drip drying and reverse embroidering are conducted, then secondary conversion and surface conditioning are conducted, a composite crystalline film layer is formed, and the problem that in the technology, powder generation and reverse rusting are prone to occurring in the film drying process is solved. According to the method, the technological process is simple, the output of waste water and solid waste is greatly reduced, the corrosion resistance and adhesive force of the obtained product are good, and the comprehensive cost is lower.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a surface pretreatment technology for iron products, and in particular to an iron product and a surface treatment method thereof. Background Art

[0002] At present, the surface treatment process of iron products is to degrease, wash with hot water, condition the surface, wash with water, then phosphate (or vitrify, silanize, etc.), wash with water, and then treat with organic coating to obtain iron products with high corrosion resistance, adhesion, cupping and impact resistance.

[0003] At present, the entire production process is complicated, and a large amount of wastewater and solid waste, including a large amount of hazardous waste, is generated during the production process, which brings a large amount of pollutants to the environment, and consumes a large amount of chemical raw materials and water, which has always restricted the development of the industry.

[0004] The applicant has proposed an electrophoretic galvanized iron product and its surface treatment method (CN114875395A), which uses a one-step degreasing chemical conversion method to remove oil stains and natural oxide films on the surface of galvanized iron products, and form a chemical conversion protective film of zinc oxalate, zinc oxide, and zinc fluoride on the surface of the product, thereby improving the corrosion resistance, anti-pollution and surface bonding ability of the product, and greatly solving the problem of low adhesion between the organic film and the product. However, iron products are different from galvanized iron products, and the treatment processes of the two products are significantly different. During the surface treatment of iron products, since iron ions are easily returned and oxidized, it is easy for powder to appear on the surface of the film, which seriously affects the performance. Summary of the invention

[0005] One of the technical problems to be solved by the present invention is to provide an iron product, the composite crystalline film layer on the surface of the iron product can obtain a morphology that is easily firmly combined with the resin paint film layer, the crystalline film layer and the resin paint film layer are linked by physical and chemical bonds, the bonding force between the resin paint and the crystalline film layer is increased, the paint film has strong adhesion, effectively blocks the diffusion rate of corrosion under the film, and extends the service life of the product.

[0006] In order to solve the above-mentioned first technical problem, the technical solution of the present invention is: An iron product, wherein a layer of chemical conversion film is formed on the surface of the iron product, wherein the chemical conversion film is a chemical conversion film containing ferrous oxalate crystals; the chemical conversion film is covered with a conversion protective film, and the chemical conversion film and the conversion protective film are composited to form a crystalline film layer.

[0007] Preferably, the conversion protective film is a protective film containing one or any combination of iron phosphate, iron sulfate, polyvinyl alcohol, iron fluoride, iron fluorozirconate, iron fluorotitanate or modified acrylic acid.

[0008] Preferably, the thickness of the crystalline film layer is 2-20 um.

[0009] The second technical problem to be solved by the present invention is to provide a surface treatment method for iron products. The method has a simple process flow, greatly reduces the amount of wastewater and solid waste generated, and improves the corrosion resistance and adhesion of the products.

[0010] To solve the above second technical problem, the technical solution of the present invention is: The surface treatment method of iron products comprises the following steps: S1. Chemical conversion for degreasing and rust removal: The iron product to be treated is placed in a chemical conversion liquid for degreasing and rust removal for 1 to 20 minutes to form a layer of ferrous oxalate crystals (FeC 2 O 4 .2H 2 O) chemical conversion film; the degreasing and rust removing chemical conversion liquid contains the following components: 30-80 g / L of oxalic acid, 0.4-3.0 g / L of ammonium bifluoride (equivalent to ammonium fluoride, hydrogen fluoride, sodium fluoride in fluorine content), and 0.002-0.01 g / L of surfactant; S2, drip-drying reverse embroidery: take out the chemically converted iron products from the degreasing and rust-removing chemical conversion liquid, and drip-dry reverse embroidery for 1 to 10 minutes; S3, secondary conversion and surface adjustment: soak or spray the iron products after dripping and reverse embroidery with conversion protection liquid to form a conversion protection film on the chemical conversion film, and the chemical conversion film and the conversion protection film are combined to form a crystalline film layer; the pH value of the conversion protection liquid is 0.5-4.

[0011] Preferably, in step S1, the temperature of the degreasing and rust removing chemical conversion liquid is 20-80°C.

[0012] Preferably, in step S1, the surfactant is one or a combination of any proportion of alkylphenol polyoxyethylene ether, octylphenol polyoxyethylene ether, nonylphenol polyoxyethylene ether, glycerol fatty acid ester, and sorbitan fatty acid ester.

[0013] As one of the solutions, in step S3, the conversion protection liquid is the degreasing and rust-removing chemical conversion liquid used in step S1.

[0014] As another solution, in step S3, the conversion protection liquid is any one of phosphoric acid, oxalic acid, sulfuric acid, citric acid, fluorozirconic acid, fluorotitanic acid or modified acrylic acid.

[0015] As another solution, in step S3, the conversion protection solution is polyvinyl alcohol, and the pH value of the polyvinyl alcohol is adjusted to 0.5-4 using phosphoric acid, oxalic acid or sulfuric acid.

[0016] Preferably, in step S3, the soaking or spraying time is 0.2 to 2 minutes.

[0017] The present invention utilizes catalytic pore-forming to generate ferrous oxalate crystal crystalline membrane, which is prone to powdering and seriously affects the performance. There are two reasons for the powdering: (1) During the membrane drying process, iron ions are very likely to return and oxidize to form powder on the membrane surface. The powdering is caused by the fluorine ion catalytic pore-forming after leaving the conversion liquid, and the oxalic acid on the membrane surface is continuously consumed. After the pH value increases, the iron ions combine with oxygen to form iron oxide, which adheres to the surface and seriously affects the combination of the conversion membrane and the resin. (2) During the chemical conversion process on the membrane surface, ferrous oxalate precipitates on the membrane surface and in the solution, resulting in powdering.

[0018] The present invention solves the problem of powdering and rusting during the membrane drying process through secondary conversion and surface conditioning. Specifically, different process requirements are met through the following different surface conditioning methods: (1) under the acidic conditions of the degreasing and rust removal chemical conversion liquid, iron oxide cannot be formed; (2) phosphoric acid, sulfuric acid, citric acid, etc. are used to quickly form acid salt precipitation in the membrane pores to inhibit the return of iron ions; (3) the intervention of strong acid is used to inhibit the catalytic function of fluoride ions and the generation of iron ions; (4) by adding polyvinyl alcohol and modified acrylic acid, the membrane pore blocking effect is increased to ensure that the membrane does not powder during drying, and the chemical bond connection is increased to improve the bonding strength; (5) the sol-gel effect of fluorozirconate (titanic) acid and its salt is used to quickly block the intergranular space and inhibit the return of iron ions.

[0019] In addition, since the treatment liquid accumulates and remains on the surface of the workpiece (especially at the lateral low surface where the liquid cannot flow out by itself in complex geometric shapes), the generation of hydrated oxalic acid crystals will have an adverse effect on the downstream process (the coating will produce pores and film bursting during the high-temperature curing process). The present invention utilizes the acidity of the conversion protection liquid (pH 0.5-4) to inhibit the formation of iron oxide on the film surface on the one hand, and at the same time utilizes the low concentration of acid radicals in the conversion protection liquid to combine with iron ions and undergo a replacement reaction with ferrous oxalate, thereby avoiding the influence of acid radical ions on subsequent processes and ensuring that no aggregation of oxalic acid crystals is generated.

[0020] Furthermore, since the complex of iron is unstable below a certain oxalic acid concentration, ferrous oxalate precipitation will form on the membrane surface, resulting in powdering (it is impossible to form hydrated ferrous oxalate crystals to form a film). If the reaction speed is too fast and the oxalic acid concentration is too low, not only will the membrane surface powder, but the solution will quickly become turbid and become scrapped and unable to form a film. In order to solve the problem of the decrease in oxalic acid concentration at the reaction interface, the present invention increases the fluidity of the interface solution and controls the reaction speed to ensure that the membrane surface does not powder during the chemical conversion process.

[0021] The presence of F ions in the chemical conversion solution of the present invention reduces the chemical energy of Fe, making it easier to generate Fe 2+ The concentration of oxalic acid is about 40 times that of hydrogen fluoride, ensuring that Fe 2+ It can generate ferrous oxalate crystals and participate in film formation. F ions act as catalysts in the reaction process and participate in film formation.

[0022] The present invention utilizes a one-step method of oil removal, rust removal, and chemical conversion. Oil removal: Grease is rapidly flocculated in the treatment liquid, and the ferrous oxalate complex ions cause the oil to rapidly precipitate and then be filtered and separated, which does not affect the performance of the treatment liquid and solves the problem of oil removal wastewater discharge. Rust removal: Iron oxide reacts with oxalic acid at the interface to generate ferrous oxalate crystals to participate in film formation, and light oil and light rust do not affect film formation and the performance of the treatment liquid.

[0023] Compared with the prior art, the present invention has at least the following beneficial effects: (1) The present invention pre-treats the surface of iron products by first using a one-step chemical conversion method for oil removal and rust removal, which can remove oil and rust from the surface of iron products. Fluoride ions and iron ions generated on the surface of iron products are captured by oxalic acid and crystallized on the surface of the products, forming a layer of ferrous oxalate crystals on the surface of the products. Then, after dripping and reverse rusting, secondary conversion and surface adjustment are performed to form a composite crystalline film layer containing ferric fluoride, ferric phosphate, ferric sulfate or polyvinyl alcohol. Through SEM+EDS detection and analysis, the chemical conversion film has a morphology that is easy to firmly combine with the organic film (with a large surface area), which can generate good adhesion between the chemical conversion film and the coating, greatly solving the problem of low adhesion between the organic film and the product, solving the surface pre-treatment of iron products under different process requirements, improving the performance indicators of the product, and increasing the life of the product. Compared with silanization and phosphating processes, the products of this method have better corrosion resistance and adhesion, and lower comprehensive costs.

[0024] (2) The present invention completes degreasing, rust removal and chemical conversion in one step, which simplifies the steps and saves the water washing step between each step in the prior art. Compared with the prior art, wastewater is reduced by 80%, solid waste is reduced by 90%, and there is no heavy metal emission. The weight of the product before treatment has not decreased but increased.

[0025] (3) Compared with the original process, the powder absorption capacity is increased by more than 20%, which greatly improves the utilization rate of powder resin. The increase in powder absorption not only reduces the overall cost, but also reduces the pollution of sedimentation powder to the environment. In the test on the same production line, the average film thickness of the resin paint is increased from 130um in the original process to 210um in this process.

[0026] (4) The film thickness of the present invention is easy to detect and can be detected by a film measuring instrument. The film color is dark gray to black and can be easily judged. Quality control is easier and more reliable, which solves the problem of being unable to quickly detect and judge the film quality in the current silanization and ceramic film production. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a surface morphology image of the chemical conversion film of the automobile steel plate detected by SEM in the present invention (magnified 1000 times); Figure 2This is a surface morphology image of the chemical conversion film of the automobile steel plate detected by SEM in the present invention (magnified 5000 times); Figure 3 This is a surface morphology image of the chemical conversion film of the automobile steel plate detected by SEM in the present invention (magnified 10,000 times); Figure 4 Yes Figure 3 EDS analysis energy spectrum of a certain point in the image; Figure 5 Yes Figure 3 EDS analysis energy spectrum of a certain point in the image; Figure 6 This is a surface morphology image of the chemical conversion film of 55CrSi spring steel detected by SEM in the present invention (magnified 2000 times); Figure 7 This is a surface morphology image (magnified 3000 times) of the chemical conversion film of 55CrSi spring steel detected by SEM after being surface-conditioned with polyvinyl alcohol and phosphoric acid; Figure 8 This is a surface morphology diagram (magnified 2000 times) of the chemical conversion film of 55CrSi spring steel detected by SEM after being surface-conditioned with sulfuric acid. DETAILED DESCRIPTION

[0028] The present invention will be further described in detail below in conjunction with the accompanying drawings and examples. In the following detailed description, only some exemplary embodiments of the present invention are described by way of illustration. Needless to say, those of ordinary skill in the art will appreciate that the described embodiments may be modified in various ways without departing from the spirit and scope of the present invention. Therefore, the descriptions in the accompanying drawings and examples are illustrative in nature and are not intended to limit the scope of protection of the claims.

[0029] like Figures 1 to 3 , Figure 6 As shown, the chemical conversion films formed after the iron products in the present invention adopt chemical conversion for oil removal and rust removal all have uniform intercrystalline morphology, and have a large surface area when combined with the resin paint film. The chemical conversion film is chemically bonded with the organic film paint to obtain a greater chemical conversion film-paint film bonding force, which can effectively improve the adhesion and impact resistance, alkali resistance, and salt spray resistance, and can more effectively prevent the expansion of the width of under-film corrosion.

[0030] like Figure 7 and Figure 8 As shown in the figure, the chemical conversion film on the surface of the product is subjected to secondary conversion and surface conditioning after drip drying, and the intercrystalline space is quickly sealed to form a composite crystalline film layer. The secondary conversion and surface conditioning can effectively inhibit the elution of iron ions, thus solving the problem that the chemical conversion film of iron products is prone to powdering and rusting during the drying process.

[0031] Respectively Figure 3 Select two points of the chemical conversion film for EDS analysis, corresponding to Figure 4 and Figure 5 The energy spectrum of , and the analysis results are shown in Table 1 and Table 2.

[0032] Table 1 element Line Type Apparent concentration k ratio Wt% Wt% Sigma Standard sample label C K-line system 3.06 0.03056 5.44 0.20 C Vit N K-line system 0.10 0.00017 0.02 0.13 BN O K-line system 10.13 0.03409 2.61 0.09 <![CDATA[SiO 2 ]]> F K-line system 6.66 0.01308 0.84 0.15 <![CDATA[CaF 2 ]]> Mg K-line system 0.01 0.00007 0.01 0.05 MgO Fe K-line system 197.54 1.97536 90.99 0.30 Fe Zr L Line 0.15 0.00145 0.09 0.12 Zr Total 100.00 Table 2 element Line Type Apparent concentration k ratio Wt% Wt% Sigma Standard sample label C K-line system 3.37 0.03369 5.72 0.19 C Vit N K-line system 0.44 0.00078 0.09 0.13 BN O K-line system 13.68 0.04602 3.40 0.09 <![CDATA[SiO 2 ]]> F K-line system 6.59 0.01293 0.82 0.14 <![CDATA[CaF 2 ]]> Mg K-line system 0.08 0.00053 0.06 0.05 MgO Fe K-line system 202.43 2.02428 89.78 0.29 Fe Zr L Line 0.20 0.00198 0.12 0.11 Zr Total 100.00 Example 1 refer to Figures 1 to 3 , iron products (taking automobile steel plates as an example), a layer of chemical conversion film is formed on the surface of the iron products, and the chemical conversion film is a chemical conversion film mainly containing ferrous oxalate crystals; the chemical conversion film is covered with a conversion protective film, and the chemical conversion film and the conversion protective film are composited to form a crystalline film layer.

[0033] The above iron product is obtained by the following surface treatment method, which comprises the following steps: S1. Chemical conversion for degreasing and rust removal: The iron product to be treated is placed in a degreasing and rust removal chemical conversion solution at 28°C, wherein the degreasing and rust removal chemical conversion solution contains the following components: 30 g / L oxalic acid, 1.2 g / L ammonium bifluoride, and 0.005 g / L glycerol fatty acid ester; the reaction tank bottom circulation is adopted, and the reaction is carried out for 12 minutes to form a layer containing ferrous oxalate crystals (FeC 2 O 4 .2H 2 O) chemical conversion film; S2, drip-dry reverse embroidery: take out the chemically converted iron products from the degreasing and rust-removing chemical conversion liquid, and drip-dry reverse embroidery for 2 minutes; S3, secondary conversion and surface adjustment: the iron products after dripping and reverse rusting are immersed or sprayed with the above-mentioned degreasing and rust-removing chemical conversion liquid for 30 seconds to form a conversion protective film on the chemical conversion film. The chemical conversion film and the conversion protective film are combined to form a crystalline film layer, and the thickness of the crystalline film layer is 5um.

[0034] Example 2 Iron products (taking automobile steel plates as an example), a layer of chemical conversion film is formed on the surface of the iron products, the chemical conversion film is a chemical conversion film mainly containing ferrous oxalate crystals; the chemical conversion film is covered with a conversion protective film, the conversion protective film is a protective film containing polyvinyl alcohol and iron phosphate; the chemical conversion film and the conversion protective film are composited to form a crystalline film layer.

[0035] The above iron product is obtained by the following surface treatment method, which comprises the following steps: S1. Chemical conversion for degreasing and rust removal: The iron product to be treated is placed in a 45°C degreasing and rust removal chemical conversion solution containing the following components: 40 g / L oxalic acid, 1.2 g / L ammonium bifluoride, and 0.003 g / L alkylphenol polyoxyethylene ether; the reaction tank bottom circulation is adopted, and the reaction is carried out for 15 minutes to form a layer of ferrous oxalate crystals (FeC 2 O 4 .2H 2 O) chemical conversion film; S2, drip-dry reverse embroidery: take out the chemically converted iron products from the degreasing and rust-removing chemical conversion liquid, and drip-dry reverse embroidery for 5 minutes; S3. Secondary conversion and surface adjustment: soak or spray the iron products after dripping and reverse embroidery with polyvinyl alcohol (pH value adjusted to 0.5-4 with phosphoric acid) for 40 seconds to form a conversion protective film on the chemical conversion film. The chemical conversion film and the conversion protective film are combined to form a crystalline film layer with a thickness of 12 um.

[0036] Example 3 Iron products (taking automobile steel plates as an example), wherein a layer of chemical conversion film is formed on the surface of the iron products, wherein the chemical conversion film is a chemical conversion film mainly containing ferrous oxalate crystals; the chemical conversion film is covered with a conversion protective film, wherein the conversion protective film is a protective film containing iron phosphate; the chemical conversion film and the conversion protective film are composited to form a crystalline film layer.

[0037] The above iron product is obtained by the following surface treatment method, which comprises the following steps: S1. Chemical conversion for degreasing and rust removal: The iron product to be treated is placed in a 60°C degreasing and rust removal chemical conversion solution containing the following components: 60 g / L oxalic acid, 0.6 g / L ammonium bifluoride, and 0.005 g / L octylphenol polyoxyethylene ether; soak for 4 minutes to form a layer of ferrous oxalate crystals (FeC 2 O 4 .2H 2 O) chemical conversion film; S2, drip-dry reverse embroidery: take out the chemically converted iron products from the degreasing and rust-removing chemical conversion liquid, and drip-dry reverse embroidery for 8 minutes; S3. Secondary conversion and surface conditioning: soak or spray the iron products after dripping and reverse embroidery with phosphoric acid for 20 seconds to form a conversion protective film on the chemical conversion film. The chemical conversion film and the conversion protective film are combined to form a crystalline film layer with a thickness of 5 um.

[0038] Example 4 refer to Figure 6 and Figure 7, iron products (taking 55CrSi spring steel as an example), a layer of chemical conversion film is formed on the surface of the iron products, and the chemical conversion film is a chemical conversion film mainly containing ferrous oxalate crystals; the chemical conversion film is covered with a conversion protective film, and the conversion protective film is a protective film containing polyvinyl alcohol and iron phosphate; the chemical conversion film and the conversion protective film are composited to form a crystalline film layer.

[0039] The above iron product is obtained by the following surface treatment method, which comprises the following steps: S1. Chemical conversion for degreasing and rust removal: The iron product to be treated is placed in a 65°C degreasing and rust removal chemical conversion solution containing the following components: 45 g / L oxalic acid, 2.8 g / L ammonium bifluoride, and 0.008 g / L glycerol fatty acid ester; the reaction is sprayed for 8 minutes to form a layer of ferrous oxalate crystals (FeC 2 O 4 .2H 2 O) chemical conversion film; S2, drip-dry reverse embroidery: take out the chemically converted iron products from the degreasing and rust-removing chemical conversion liquid, and drip-dry reverse embroidery for 2 minutes; S3. Secondary conversion and surface adjustment: soak or spray the iron products after dripping and reverse embroidery with polyvinyl alcohol (pH value adjusted to 0.5-4 with phosphoric acid) for 20 seconds to form a conversion protective film on the chemical conversion film. The chemical conversion film and the conversion protective film are combined to form a crystalline film layer with a thickness of 8 um.

[0040] Example 5 refer to Figure 6 and Figure 8 , iron products (taking 55CrSi spring steel as an example), a layer of chemical conversion film is formed on the surface of the iron products, and the chemical conversion film is a chemical conversion film mainly containing ferrous oxalate crystals; the chemical conversion film is covered with a conversion protective film, and the conversion protective film is a protective film containing ferric sulfate; the chemical conversion film and the conversion protective film are composited to form a crystalline film layer.

[0041] The above iron product is obtained by the following surface treatment method, which comprises the following steps: S1. Chemical conversion for degreasing and rust removal: The iron product to be treated is placed in a 40°C degreasing and rust removal chemical conversion solution containing the following components: 45 g / L oxalic acid, 2.8 g / L ammonium bifluoride, and 0.008 g / L glycerol fatty acid ester; the reaction is sprayed for 8 minutes to form a layer of ferrous oxalate crystals (FeC 2 O 4 .2H 2 O) chemical conversion film; S2, drip-dry reverse embroidery: take out the chemically converted iron products from the degreasing and rust-removing chemical conversion liquid, and drip-dry reverse embroidery for 1 minute; S3, secondary conversion and surface conditioning: the iron products after dripping and reverse embroidery are soaked or sprayed with sulfuric acid for 20 seconds to form a conversion protective film on the chemical conversion film. The chemical conversion film and the conversion protective film are combined to form a crystalline film layer, and the thickness of the crystalline film layer is 7um.

[0042] In order to verify the corrosion resistance and adhesion of products obtained by different surface treatment processes, the iron product (taking 55CrSi spring steel as an example) prepared in Example 4 of the present invention and the iron product (taking 55CrSi spring steel as an example) prepared by the traditional phosphating and silanization process are compared in a salt spray test. The specific test process is as follows: (1) Sample description: The iron product prepared in Example 4 was dried, sprayed and cured on the production line to obtain the sample of the present invention (hereinafter referred to as the oxalated sample), the phosphating sample obtained by the phosphating process and the silanizing sample obtained by the silanization process.

[0043] (2) Film thickness description: The film thickness of the oxalate sample is 150-240um, the film thickness of the phosphate sample is 70-120um, and the film thickness of the silanized sample is 240-340um.

[0044] (3) Incision description: Use a small hacksaw to cut the paint film of each spring sample, cutting to the spring metal substrate, with a cut size of approximately 1.2 to 1.8 mm.

[0045] After the sample was cut, the salt spray test results were as follows: 378h: The spring ports of all samples were corroded to varying degrees, and the cuts did not expand significantly. The phosphating and oxalating samples did not show pitting corrosion, and the silanization samples showed bubbling corrosion with corrosion points greater than 0.5 mm. Due to the continued salt spray test, the spring ports and cuts were not cleaned.

[0046] 936h: The spring ports of all samples were corroded to varying degrees. The port corrosion degree of the silanized sample was lower than that of the phosphating and oxalating samples. The spring cuts did not expand significantly. The phosphating, silanizing and oxalating samples all showed rust pitting corrosion. The rust pitting of the silanizing and oxalating samples was mainly concentrated on the ports. The phosphating samples showed rust pitting corrosion earlier and more, and rust pitting corrosion also appeared in the middle of the spring. The silanized samples showed bubbling corrosion with corrosion points greater than 0.5 mm. The phosphating and oxalating samples did not show bubbling corrosion. Because the salt spray test was continued, the spring ports and cuts were not cleaned.

[0047] 1753h: The spring ports of all samples were corroded to varying degrees. The corrosion degree of the ports of the oxalated samples was significantly lower than that of the phosphating and silanizing samples. The corrosion of the ports of the phosphating and silanizing samples was mainly concentrated between the hook position and the port, showing a trend of large-scale expansion from the hook position to the port. No corrosion expansion was observed in the oxalated samples. The adhesion of the spring cut was tested by peeling. The phosphating spring sample had large-scale peeling, while the adhesion of the cut position of the oxalating and silanizing spring samples was not significantly reduced.

[0048] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. Iron products, characterized in that: A layer of chemical conversion film is formed on the surface of the iron product, and the chemical conversion film is a chemical conversion film containing ferrous oxalate crystals; the chemical conversion film is covered with a conversion protective film, and the chemical conversion film and the conversion protective film are combined to form a crystalline film layer.

2. The iron product according to claim 1, characterized in that: The conversion protective film is a protective film containing one or any combination of iron phosphate, iron sulfate, polyvinyl alcohol, iron fluoride, iron fluorozirconate, iron fluorotitanate or modified acrylic acid.

3. The iron product according to claim 1, characterized in that: The thickness of the crystalline film layer is 2-20 um.

4. A method for surface treatment of iron products, characterized in that: The steps include: S1, degreasing and rust removal chemical conversion: placing the iron product to be treated in a degreasing and rust removal chemical conversion liquid to react for 1 to 20 minutes, forming a chemical conversion film containing ferrous oxalate crystals on the surface of the iron product; the degreasing and rust removal chemical conversion liquid contains the following components: 30 to 80 g / L of oxalic acid, 0.4 to 3.0 g / L of ammonium bifluoride, and 0.002 to 0.01 g / L of a surfactant; S2, drip-drying reverse embroidery: take out the chemically converted iron products from the degreasing and rust-removing chemical conversion liquid, and drip-dry reverse embroidery for 1 to 10 minutes; S3, secondary conversion and surface adjustment: soak or spray the iron products after dripping and reverse embroidery with conversion protection liquid to form a conversion protection film on the chemical conversion film, and the chemical conversion film and the conversion protection film are combined to form a crystalline film layer; the pH value of the conversion protection liquid is 0.5-4.

5. The surface treatment method of an iron product according to claim 4, characterized in that: In step S1, the temperature of the degreasing and rust removing chemical conversion liquid is 20-80°C.

6. The surface treatment method of an iron product according to claim 4, characterized in that: In step S1, the surfactant is one or a combination of any proportion of alkylphenol polyoxyethylene ether, octylphenol polyoxyethylene ether, nonylphenol polyoxyethylene ether, glycerol fatty acid ester, and sorbitan fatty acid ester.

7. The surface treatment method of an iron product according to claim 4, characterized in that: In step S3, the conversion protection liquid is the degreasing and rust-removing chemical conversion liquid used in step S1.

8. The surface treatment method of an iron product according to claim 4, characterized in that: In step S3, the conversion protection liquid is any one of phosphoric acid, oxalic acid, sulfuric acid, citric acid, fluorozirconic acid, fluorotitanic acid or modified acrylic acid.

9. The surface treatment method of an iron product according to claim 4, characterized in that: In step S3, the conversion protection solution is polyvinyl alcohol, and the pH value of the polyvinyl alcohol is adjusted to 0.5-4 using phosphoric acid, oxalic acid or sulfuric acid.

10. The surface treatment method of an iron product according to claim 4, characterized in that: In step S3, the soaking or spraying time is 0.2 to 2 minutes.

Citation Information

Patent Citations

  • Electrophoretic galvanized iron product and surface treatment method thereof

    CN114875395A